A cross-sectional study exploring general practitioners’ views on dietary supplements - Sophia Wagner; Sascha Eickmann; Hansjörg Baurecht; Anne Herrmann (BMC Primary Care)
Abstract Background Dietary supplements (DS) are often used by patients to enhance their health and well-being. General practitioners (GPs) are commonly the first point of contact for patients who enquire about DS. The aim of this study was to explore GPs’ views on DS. Methods A cross-sectional purposeful recruitment online survey of 162 general practitioners (GPs) in Germany was conducted between May and August 2021. The questionnaire assessed GPs’ views on dietary supplements (DS), including perceptions of safety, efficacy, and importance in medical practice. Data were analyzed using inferential statistics and logistic regression analyses to explore associations between GPs’ views and demographic factors. Results Response rate could not be determined because multipliers were included here by means of personal networks, consent rate was 100%. Many respondents considered DS to be an important topic in their daily practice (64,8%, n = 99). Almost two thirds were convinced of their efficacy and considered DS to be safe for use (61,2%, n = 93). However, the majority of respondents were in favor of more standardized guidelines (86.8%, n = 132) and improved medical education on the handling of DS in routine care (89,5%, n = 136). Physicians who self-administered DS were statistically significantly more likely to perceive them as safe to use, with an OR of 4.25 (95% CI: 1.74–10.40). Self-administration [OR 4.52 (1.67–12.22)] and participation in continuous medical education (CME) [OR 3.52 (1.133–9.38)] were positively associated with perceiving them as an important topic. Conclusions To the best of our knowledge, this is the first study to assess German GPs’ perceptions regarding DS. The majority of physicians recognized the importance of DS in routine care but wished for improved regulation and more standardized guidelines regarding their use. The findings could be used to develop targeted educational interventions and improve handling of DS in daily general practice.